Risk Factors in Descending Necrotizing Mediastinitis Following Submandibular Abscess at dr. Cipto Mangunkusumo Hospital in January 2012 – July 2016 - Putra, Muhammad Arza; Pratama, Raditya; Kekalih, Aria (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Descending necrotizing mediastinitis (DNM) encountered problem of a high mortality rate. The increasing number of incidence and the need of immediate intervention DNM cases urge surgeons to manage early preventions and adequate therapy. The purpose of thisstudy is to find risk factors that correlate to the incidence of DNM in submandibular abscess patients. Method. Cross sectional study conducted enrolling all patients diagnosed with submandibular abscess that developed to DNM and treated surgically in emergency operating theater in period of January 2012 to July 2016 were reviewed. Mediastinitis which was not following submandibular abscess, those were not treated surgically or treated by other than the division of thoracic and cardiovascularsurgery, and those of pediatrics were not included on the study. The incidence of DNM was the dependent variable on the study; risk factors such as gender, age, body mass index (BMI), comorbid(s), leukocyte counts, and microorganism(s) were independent variables on the study. Results. There were 68 subjects enrolled on the study. The met the inclusion and exclusion criteria. Subjects characteristics are shown in table 1. Septic condition, surgical intervention, postoperative complications, and mortality are shown in table 2. There was no correlation between gender (p = 0.656), age (p = 0.763), comorbid(s) (p = 0.767 and 0.952). It also found that leukocyte counts, and cultured microorganism(s) showed no significant correlation. Conclusion. Not a single risk factor specifically correlatesto the incidence of DNM in subjects with submandibular abscess. Thus, so those with submandibular abscess have a same risk to have DNM developed.